Metallic phase enabling MoS2 nanosheets as an efficient sonosensitizer for photothermal-enhanced sonodynamic antibacterial therapy - Huizhi Chen; Xiaojun He; Zhan Zhou; Zhikang Wu; Hai Li; Xinsheng Peng; Yubin Zhou; Chaoliang Tan; Jianliang Shen (Journal of Nanobiotechnology, 2022)
Abstract Two-dimensional (2D) transition metal dichalcogenide (TMD) nanosheets (e.g., MoS2) with metallic phase (1T or 1T´ phase) have been proven to exhibit superior performances in various applications as compared to their semiconducting 2H-phase counterparts. However, it remains unclear how the crystal phase of 2D TMD nanosheets affects their sonodynamic property. In this work, we report the preparation of MoS2 nanosheets with different phases (metallic 1T/1T´ or semiconducting 2H) and exploration of its crystal-phase effect on photothermal-enhanced sonodynamic antibacterial therapy. Interestingly, the defective 2D MoS2 nanosheets with high-percentage metallic 1T/1T´ phase (denoted as M-MoS2) present much higher activity towards the ultrasound-induced generation of reactive oxygen species (ROS) as compared to the semiconducting 2H-phase MoS2 nanosheets. More interestingly, owing to its metallic phase-enabled strong absorption in the near-infrared-II (NIR-II) regime, the ultrasound-induced ROS generation performance of the M-MoS2 nanosheets can be further enhanced by the photothermal effect under a 1064 nm laser irradiation. Thus, after modifying with polyvinylpyrrolidone, the M-MoS2 nanosheets can be used as an efficient sonosensitizer for photothermal-enhanced sonodynamic bacterial elimination under ultrasound treatment combining with NIR-II laser irradiation. This study demonstrates that metallic MoS2 nanosheets can be used as a promising sonosensitizer for antibacterial therapy, which might be also promising for cancer therapies. Graphical Abstract